2008
DOI: 10.1111/j.1440-1797.2008.00950.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the prognostic value of the risk, injury, failure, loss and end‐stage renal failure (RIFLE) criteria for acute kidney injury

Abstract: SUMMARY Aim:The experts have argued about the use of the risk, injury, failure, loss and endstage renal failure (RIFLE) criteria as a prognosis scoring system. We examined the association between in-hospital mortality and the RIFLE criteria, and discussed its accuracy as a prognosis factor. Methods:In this prospective study, we analysed the data gathered from a cohort of 956 patients admitted in a Spanish tertiary hospital between January 1998 and April 2006. Hazard ratios for mortality, and survival curves wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
14
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 29 publications
4
14
1
Order By: Relevance
“…RIFLE class L was also associated with higher 1-year mortality in our study, which is similar to previous findings [27,49,50]. Age, severe RIFLE class, etiology of AKI and prior CKD have been shown to be independent factors for higher risk of 1-year mortality in several studies [22,27,39] and in an extensive meta-analysis [29]. In the present study, RIFLE class L, older age and prior CKD - but not etiology of AKI - were identified as independent risk factors for 1-year mortality.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…RIFLE class L was also associated with higher 1-year mortality in our study, which is similar to previous findings [27,49,50]. Age, severe RIFLE class, etiology of AKI and prior CKD have been shown to be independent factors for higher risk of 1-year mortality in several studies [22,27,39] and in an extensive meta-analysis [29]. In the present study, RIFLE class L, older age and prior CKD - but not etiology of AKI - were identified as independent risk factors for 1-year mortality.…”
Section: Discussionsupporting
confidence: 83%
“…Oliguria was associated with hospital death in our study and in others [48], but we did not found an association with 1- and 10-year mortalities. RIFLE class L was also associated with higher 1-year mortality in our study, which is similar to previous findings [27,49,50]. Age, severe RIFLE class, etiology of AKI and prior CKD have been shown to be independent factors for higher risk of 1-year mortality in several studies [22,27,39] and in an extensive meta-analysis [29].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Consequently, they recommended that an estimated baseline creatinine be calculated using the Modification of Diet in Renal Disease (MDRD) formula (11) with an assumed GFR for all patients between 75 and 100 ml/min. As a tool for post hoc analysis in research studies, this back-calculation method has become widespread, with most studies adopting 75 ml/min (5,8,(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). A few epidemiologic studies have used an estimated baseline for all of their patients (e.g., those using the Australian and New Zealand Intensive Care Society database (5,(12)(13)(14)), whereas in other studies the proportion of patients for whom a baseline is estimated by back-calculation is as low as 7% (19).…”
mentioning
confidence: 99%
“…In 2010, Zavadá and colleagues introduced the Pittsburgh Linear Three Variables (PLTV) formula, which uses the same anthropometric variables as the MDRD equation and has shown promising results (8). To estimate the bSCr with all these formulae, we assume that the GFR is equivalent to a standard GFR of 75 ml/min per 1.73 m 2 (1,4,9,10). However, use of a standard GFR is not appropriate because there is high variability in the GFR within a given population due to age or gender.…”
Section: Introductionmentioning
confidence: 99%